Analysis of Student Understanding Related to Environmental Literature in Elementary School with Science Technology Community Approach - Muhammad Nur Hudha; Endah Vennita Rahayu Putri; Farida Nur Kumala (PAEDAGOGIA, 2021)
The purpose of this study was to determine students' understanding of environmental literacy and the application of the Community Science Technology (STM) approach in elementary schools. The focus of the research is the application of the STM approach to improving the environmental literacy of third-grade students in an elementary school in Malang. The aspects used are based on environmental literacy indicators, including aspects of cognitive abilities and affective abilities. The research method used is a case study with a qualitative approach. The instruments used are observation, interviews, and documentation. The data analysis used refers to the Miles & Huberman model, which has three steps in analyzing the data: Data Reduction, Data Presentation, and Conclusion Drawing/Verification. The results showed that applying the STM approach could improve student learning outcomes. Student learning outcomes on aspects of cognitive abilities and affective abilities can be said to be good. The results of this completeness can conclude that the STM approach can improve student learning outcomes, especially in the aspect of environmental literacy.